Activity predication of rhodomyrtus tomentosa (Aiton) hassk against ace1 inhibitors - Samsul Hadi; Kunti Nastiti (Institute of Computer Science (IOCS), 2023)
ACE is a peptidyl-dipeptidase enzyme that catalyzes the conversion of substrates from angiotensin I to angiotensin II. These changes cause constriction of blood vessels so that blood pressure increases (hypertension), so This study aims to find compounds that have the potential to reduce blood pressure through the pathway of ACE1 enzyme inhibition. The method used is docking, the material used is a compound contained from Rhodomyrtus tomentosa and. The ACE1 protein was obtained from RCSB with the code 1UZF. The equipment used was an online pass webserver, PLNTS software and discovery studio. This research was started by redocking the native ligand to determine the coordinates and radius, followed by validating the docking results. The results of the early stage screening obtained 4 compounds with a threshold value above 0.3, these four compounds were continued with the docking test. The docking scores obtained were Afrormosin (-59.620); Pedunculagin (-45.205); Tomentosine (-70.986); Desgalloylstachyurin (-54.374). The conclusion obtained is that the Tomentosine compound binds most easily to ACE1